2018
DOI: 10.1111/hae.13534
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic bypassing agent use before and during immune tolerance induction in patients with haemophilia A and inhibitors to FVIII

Abstract: The development of high-titre inhibitory antibodies (inhibitors) against factor VIII (FVIII) remains a challenge in the management of patients with haemophilia A (HA). Patients with high-titre inhibitors are more likely to experience uncontrolled bleeding, physical disability from chronic arthropathy and premature death compared with those without this complication. Immune tolerance induction (ITI), utilizing repeated infusions of FVIII, is an effective therapeutic approach to eliminating inhibitory antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
5
1
Order By: Relevance
“…There is limited literature available that specifically evaluates the use of prophylaxis with BPA prior to or while patients are receiving ITI and to the authors' best knowledge, no comparative trials of bypassing agents used as prophylaxis in patients with Haemophilia A and inhibitors to FVIII are currently available in the literature. Evidence from the study data that is available has demonstrated that concomitant administration of BPA prophylaxis during ITI leads to a decrease in bleeding events [11][12][13]. Published case reports second this by providing evidence of successful use of prophylaxis in patients prior to or during ITI, contradictory to our findings.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…There is limited literature available that specifically evaluates the use of prophylaxis with BPA prior to or while patients are receiving ITI and to the authors' best knowledge, no comparative trials of bypassing agents used as prophylaxis in patients with Haemophilia A and inhibitors to FVIII are currently available in the literature. Evidence from the study data that is available has demonstrated that concomitant administration of BPA prophylaxis during ITI leads to a decrease in bleeding events [11][12][13]. Published case reports second this by providing evidence of successful use of prophylaxis in patients prior to or during ITI, contradictory to our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…One study reported the bleeding rates of prophylaxis and on-demand cohorts with BPA for six months, and found that with the prophylaxis BPA cohort bleeding rates were significantly reduced compared to the on-demand cohort [ 10 ]. Similarly, according to the literature, patients with Haemophilia A and inhibitors to FVIII who experience acute bleeding events during ITI and are managed with on-demand bypassing therapies will almost inevitably lead to the development and/or worsening of haemophilic arthropathy [ 11 ]. Looking at the baseline results of the patients in this study, the prophylaxis cohort had higher mean bleeding and joint bleeding events prior to the most recent inhibitor (as shown in Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 Prophylactic use with these compounds indeed reduces the annual bleeding rate in these inhibitor patients. [9][10][11][12] It should be noted that the circulatory halflives of these products are relatively short (4-7 hours for FEIBA and 1.5-2.7 hours for NovoSeven), albeit that extravasation of rFVIIa may prolong its clinical efficiency. 13 More recently, other therapeutic approaches have been developed, including the bispecific antibody Emicizumab (Hemlibra, F. Hoffmann-La Roche, Ltd, Basel, Switzerland) and Fitusiran (Sanofi-Genzyme/Alnylam, Cambridge, Massachusetts, United States), a small interfering RNA (siRNA) approach that reduces antithrombin expression.…”
Section: Introductionmentioning
confidence: 99%